The Learning Style for distinguished students and their ordinary mates in the secondary stage in accordance to some variables - شروق كاظم سلمان سهام علي عبدالله (College of Education for Women, 2019)
The current problem is summarized in what is called the development failing experience in comprehencing the studying materials , so the students will feel worry of repeating failure in he future , so he would seek blind keeping on heart for the studying material bond this isbad due to the forgetting in the future , one side of thesis research problem is that there is many contradictory researches result in relation to the learning styles which impose the nessicity to find results lessen this contradiction . the importance of the research is summarized in the importance of the subject under the study , in that the researcher ( as in her knowledge ) did not find a thesrs tackling the subject of the distinguished students in comporsion to their ordinary mates and according to the gender variable , and this might constitute an addition to the psychological studies . the research aimed to :- 1- Measure learning styles among total sample of exceptional and ordinary schools comparing to hypothetical mean for the subscales ( meaning learning style , processing learning style and symbolic learning style ) . 2- Measure learning styles among the sample comparing to the hypothetical mean for the subscales ( meaning learning style , processing learning style and symbolic learning style ) according to ( exceptional - ordinary ) and ( meal - female ) . And the research aimed to identify :- 1- There is no significant differences of the sex ( meal - female ) on the type of school (exceptional - ordinary ) depend on the meaning learning styles among secondary school students . 2- There is no significant differences of the sex ( meal - female ) on the type of school (exceptional - ordinary ) depend on the processing learning styles among secondary school students . 3- There is no significant differences of the sex ( meal - female ) on the type of school (exceptional - ordinary ) depend on the symbolic learning styles among secondary school students . The researcher support her study by a theoretical frame of memory , and talking to information processing theory and learning styles. the researcher had depend on ( Tulving , 1972 ) as learning styles scale and this scale consisted of three styles( meaning learning style , processing learning style and symbolic learning style ) , and the scale which was consisted of 30 item for each style 10 items and with three answers , the scale was applied on the fifth class scientific high school and sample consisted of 400 students in 200 distinguished students and 200 ordinary students who were choose randomly , and to deal with data statistically we use number of statistical means like difference analysis " T- test and person coefficient.. act . After the analysis the researcher had reached to number of result some of which the exceeding of the distinguished students in each of the above mentioned learning styles and there is no existence of the effect of gender variable on the learning styles among high school students , in addition there is no interactive effect between school type variable on the average marks of learning styles for high school students , and had number of recommendations and number of suggestions which some of which are exploring learning styles in academic stages like university and according to college and studying field .